Eumycetoma caused by Alternaria alternata in an immunocompetent host: A rare case report - Vasudha A Belgaumkar; Ravindranath Brahmadeo Chavan; Vijay Vidyadhar Raut; Pallavi Prataprao Patil (Wolters Kluwer Medknow Publications, 2020)
Mycetoma is a chronic granulomatous subcutaneous infection caused by either true fungi (eumycetoma) or filamentous anaerobic bacteria (actinomycetoma). Herein, we report a case of mycetoma foot due to a rare opportunistic fungus in a male farmer. He presented with swelling and sinuses discharging pus and bloodstained black granules on the right foot for 6 years. A final diagnosis of eumycetoma (caused by Alternaria alternata) with bone involvement in immunocompetent patient was confirmed on the basis of histopathology and culture. Opportunistic fungi most commonly cause infection in immunocompromised hosts. Although mycetoma caused by opportunistic and saprophytic fungi responds relatively well to systemic antifungal treatment, few cases such as ours might require amputation. Clinically, it is difficult to comprehend the exact etiological agent. Proper diagnosis and radiological investigation are necessary for the precise identification of the etiological agent and extent of spread which in turn dictate choice of treatment.